Elaboración de un plan de marketing para la cooperativa de ahorro y crédito Cacpe Zamora, cantón Zamora, provincia de Zamora Chinchipe, para el año 2017. - SAETAMA BARROS, LILIANA ISABEL (2017)
The present thesis work has as a general objective "Propose a Marketing Plan for the Cooperativa Cacpe Zamora, Zamora Canton, Zamora Chinchipe Province, within the methods that were used are the inductive, deductive, statistical, descriptive and analytical; as well as the use of research techniques such as: Observation, Interview and Survey. For the development of the present investigative work, several topics were addressed that were determined as follows: Situational analysis of the Cacpe Zamora Cooperative which allowed to obtain a clear vision of the current reality of the Cooperative, analysis of external factors or macro environment of the Cooperativa, for this the following factors were analyzed: Political, economic, social, technological, in the same way the 5 forces of Porter were analyzed, in the same way the internal analysis was carried out, for this an interview was applied to the Manager and a series of surveys to the internal and external clients of the Cooperative, this information was the support to determine the EFI matrix, which shows that the Cooperative takes advantage of its strengths and minimizes its weaknesses. At the end of this thesis work can be concluded by saying that: The Cooperative has a quality financial service because it satisfies the service to the members, and the recommendation for the Cooperative would be to continue offering the quality financial service, so that it can continue attracting more members